Oxygen radicals and nitric oxide levels in chondral or meniscal lesions or both - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2002)
The pathophysiologic mechanism of osteoarthritis is not well known. The importance of reactive oxygen species and nitric oxide in the pathogenesis of osteoarthritis in patients with chondral or meniscal lesions or both and a search for their source were investigated. Synovial fluid samples obtained from 44 patients with osteoarthritis (16 had meniscal lesions, 12 had chondral lesions, and 16 had meniscal plus chondral lesions) were analyzed. Ten control subjects also were included. Reactive species, nitric oxide, and peroxynitrite were measured by the chemiluminescence technique. Patients with chondral lesions had significantly increased levels of O-2-when compared with patients with meniscal lesions and the control group. However, patients with chondral or meniscal plus chondral lesions had significantly higher levels of other reactive oxygen species when compared with the control group. For the patients with meniscal plus chondral lesions, the contribution of nitrogen containing reactive species was evident. Although patients with chondral lesions had a significant increase in nitric oxide, the increase in patients with meniscal plus chondral lesions was more pronounced in peroxynitrite concentration. These reactive species will lead to tissue damage along with the mechanical damage caused by meniscal or chondral lesions or both.
Keywords: IN-VIVO; SYNOVIAL-FLUID; ARTHRITIS; OSTEOARTHRITIS; CHONDROCYTES; INFLAMMATION; EXPRESSION; SYNTHASE